Sistem Informasi Rekam Medis Asesmen Kebidanan Berbasis Web Menggunakan Metode Rapid Aplication Development (RAD) - Wahyu Fajri; Tikaridha Hardiani (UNIB Press, 2023)
The PKU Muhammadiyah Gamping Hospital - Yogyakarta has the goal that processes related to administrative and documentation aspects are digitized immediately. Medical record officers at PKU Muhammadiyah Gamping Hospital - Yogyakarta, especially in the field of midwifery assessment, still use a manual system in managing and preparing patient data reports. This causes delays in submitting daily patient data reports and has an impact on reducing patient services. To overcome this, a digital recording device is needed, namely a web-based medical record information system. The method used by the author in developing this information system is using the RAD or Rapid Application Development model. The programming platform uses the CodeIgniter 3 framework and Bootstrap 4.6. Database management using MySQL. The purpose of creating this medical record information system is to facilitate the management of patient data which includes patient registration data, patient medical record recording data, and collection of patient master data. This medical record system is expected to improve midwifery assessment services. Keywords: Medical Record Information System, Midwifery Assessment, RAD, Digitalization.